REKAM JEJAK ALUMNI AHWAL SYAKHSHIYYAH DI MASYARAKAT (STUDI PELACAKAN ALUMNI [TRACER STUDY] PROGRAM STUDI AHWAL SYAKHSHIYYAH STAIN JURAI SIWO METRO) - Wijayati, Mufliha (JURNAL TAPIS, 2015)
ABSTRACTAkhwal Syakhshiyyah (AS) is the oldest course in the faculty of Syaria STAIN Jurai Siwo Metro and is the founding pioneer of the establishment of STAIN Jurai Siwo Metro in 1997. Scientific knowledge developed by AS is scientific sharia (Islamic law) at a concentration of family law study. The output of AS course, since 1997-2013, was 191 graduates (data recorded), who spread over several districts in Lampung province, and some parts of outside Lampung. To view the extent to which graduates of the AS course can be beneficial to the community in accordance with its core competencies, a tracking study has been conducted. The tracking study was conducted by surveying all graduates in the latest five years, 2009-2013, amounting to 90 alumni. Data were collected through documentation, questionnaire, and observation. Theresult of the alumni tracking study showed that the AS alumni work in a relatively diverse career ranging from Lecturer, Registrar in PA, KUA Employee, marketing, employees, and teachers. However, alumni who work in the area of core competencies are still very limited; most alumni work in the field of education and Islamic financial institutions. Hence, the relevance and competence in relation to the needs of the working should be reviewed to minimize the gap between the field of higher education with the employment.Â Keywords: Alumni, tracking study, ahwal shakhsiyyah